2004
DOI: 10.1109/mis.2004.61
|View full text |Cite
|
Sign up to set email alerts
|

Creating an Ambient-Intelligence Environment Using Embedded Agents

Abstract: A mbient intelligence is an exciting new information technology paradigm in which people are empowered through a digital environment that is aware of their presence and context and is sensitive, adaptive, and responsive to their needs. 1 Ambient-intelligence environments are characterized by their ubiquity, transparency, and intelligence. In these environments, a multitude of interconnected, invisible embedded systems, seamlessly integrated into the background, surround the user. The system recognizes the peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
154
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(157 citation statements)
references
References 3 publications
2
154
0
1
Order By: Relevance
“…The iDorm project of Hagras, et al [66] is another of these notable projects that has realized a fully-implemented automated living environment. In this case, the setting is a campus dorm environment.…”
Section: Decision Makingmentioning
confidence: 99%
See 1 more Smart Citation
“…The iDorm project of Hagras, et al [66] is another of these notable projects that has realized a fully-implemented automated living environment. In this case, the setting is a campus dorm environment.…”
Section: Decision Makingmentioning
confidence: 99%
“…A common interface to the iDorm and its devices is implemented through Universal Plug and Play (UPnP), and any networked computer running a standard Java process can access and control the iDorm directly [66]. Fuzzy rules are learned from observing resident activities [67] and are used to control select devices in the dorm room.…”
Section: Smart Homesmentioning
confidence: 99%
“…In [46], the authors used a fuzzy rule-based controller where the output of the rules is not a class but a function in order to monitor a smart environment, called "iDorm", based on preferences of the occupants. The data was generated over two months by recording two student activities in a dormitory flat which is equipped with 11 sensors: internal light level, external light level, internal temperature, external temperature, chair pressure, bed pressure, occupancy and time etc.…”
Section: Fuzzy Logicmentioning
confidence: 99%
“…The study demonstrated how fuzzy rules can be continuously generated online to meet the requirements of a dynamic environment. The author used the iDorm data [46]. The data was split into two subsets: the training set contains 75% samples for the first month, and The testing set contains 25% of the first month and all samples of the second month.…”
Section: Fuzzy Logicmentioning
confidence: 99%
“…In contrast, the approach taken by the iDorm project [19] is to use a fuzzy expert system to learn rules that replicate inhabitant interactions with devices, but will not find an alternative control strategy that improves on manual control for considerations such as energy expenditure.…”
Section: Overview Of the Mavhome Smart Homementioning
confidence: 99%